Caracterização estrutural da mineralização da mina de Fazenda Nova - GO - Terra, Cícero Fonte Boa [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The study area is includes in the geological context of Arenópolis Magmatic Arc, a region where there are neoproterozoic associations of granodioritic and tonalitic composiotion. (Ortogneisses of the western Goiás) and sequences metavolcanic-sedimentary (Jaupaci Metavolcanic-sedimentary Sequence ). In the mapped area, both units are covered by a cover-laterite. The Ortogneisses from Goiás West consist of a source granodioritic gneisses, corresponding to the Biotite granodiorite gneisse, and also by tonalitic gneiss composition corresponding to Metatonalit. The Jaupaci Metavolcanic-sedimentary Sequence is formed by Chlorite Schist (Metabasalt), Biotite Schist (Metadacite) and Sericite Schist (Metarhyolite), and even intrusions Sin/Tardi e Post Tectonic, granite to diorite composition (Diorites), and alson tonalitic (Bacilandia Tonalite). Post tectonic intrusions are observed, wich were Hornblend Diorite Porphyry and Lamprophyres, Structural analysis allowed the identification of three deformational events, Dn-1, Dn and Post-Dn. The first event is associated with a bygone foliation, lineation which generates an intersectional event, generating the foliation Sn, this being the most important structure in the study area, generating even the type mineral lineation and stretch. The last deformational event is characterized by folds on different scales, affecting the Sn foliation. The rocks of the region have features s active hydrothermal and regional metamorphism, and are composed os assembly indicative of mineralogical facies metamorphism Green Schist, in chlotite zone, with evidence of retro metamorphism. Locally there are sulfides as pyrite, arsenopyrit and pyrhotite, and te mineralization is associated with the arsenopyrite

A área de estudo esta inserida no contexto geológico do Arco Magmático de Arenópolis, região onde ocorrem associações neoproterozóica de composição tonalítica a granodioritica (Ortognaisses do Oeste de Goiás) e ainda sequencias metavulcanosedimentares (Sequencia Metavulcano-sedimentar de Jaupaci). Na área mapeada ambas as unidades encontram-se recobertas por uma cobertura detrito-laterítica. O Ortognaisse do Oeste de Goiás é formado por um gnaisse de origem granodiorítica, correspondendo ao Biotita Gnaisses Granodioritico, e também por gnaisse de composição tonalítica, correspondendo ao Metatonalito. A Sequência Metavulcano-sedimentar de Jaupaci é formada por Clorita Xisto (Metabasalto), Biotita Xisto (Metadacito) e Sericita Xisto (Metariolito), e ainda intrusões sin/tardi tectônica de composição granítica a diorítica (Dioritos), e também tonalítica (Tonalito Bacilândia). Intrusões pós-tectônica são observadas, sendo elas Hornblenda diorito pórfiro e lamprofiros. Análises estruturais permitiram identificar três eventos deformacionais; Dn-1, Dn e Pós-Dn. O primeiro evento está associado a uma foliação pretérita, a qual gera uma lineação de intersecção com a foliação principal. O segundo evento é caracterizado por ser o principal evento deformacional, gerando a foliação Sn, esta sendo a estrutura mais marcante na área de estudo, gerando ainda lineação do tipo mineral e de estiramento. O ultimo evento deformacional caracteriza-se por dobras em escalas diferenciadas, afetando a foliação Sn. As rochas de região apresentam feições de metamorfismo regional e hidrotermal atuantes, e são compostas por assembleia mineralógica indicativa de metamorfismo facies xisto verde, zona da clorita, com evidencias de retrometamorfismo. Localmente ocorrem sulfetos como pirita, arsenopirita e pirrotita, sendo a mineralização associada a arsenopirita
Keywords: Gnaisse; Geologia estrutural; Ouro; Cisalhamento; Fazenda Nova (GO); Gneiss; Structural geology; Gold